7q31.2q31.31 deletion downstream of FOXP2 segregating in a family with speech and language disorder - Rieger, Melissa; Krumbiegel, Mandy; Reuter, Miriam; Schützenberger, Anne; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2020)
Chromosomal 7q31 deletions have been described in individuals with variable neurodevelopmental phenotypes including speech and language impairment. These copy number variants usually encompass FOXP2, haploinsufficiency of which represents a widely acknowledged cause for specific speech and language disorders. By chromosomal microarray analysis we identified a 4.7 Mb microdeletion at 7q31.2q31.31 downstream of FOXP2 in three family members presenting with variable speech, language and neurodevelopmental phenotypes. The index individual showed delayed speech development with impaired speech production, reduced language comprehension, and additionally learning difficulties, microcephaly, and attention deficit. His younger sister had delayed speech development with impaired speech production and partially reduced language comprehension. Their mother had attended a school for children with speech and language deficiencies and presented with impaired articulation. The deletion had occurred de novo in the mother, includes 15 protein-coding genes and is located in close proximity to the 3′ end of FOXP2. Though a novel locus at 7q31.2q31.31 associated with mild neurodevelopmental and more prominent speech and language impairment is possible, the close phenotypic overlap with FOXP2-associated speech and language disorder rather suggests a positional effect on FOXP2 expression and function.
CRIS-Team Scopus Importer:2020-09-11
Keywords: 7q; deletion; FOXP2; language; speech

Aberrant phase separation and nucleolar dysfunction in rare genetic diseases - Mensah, Martin A.; Niskanen, Henri; Magalhaes, Alexandre P.; Basu, Shaon; Kircher, Martin; Sczakiel, Henrike L.; Reiter, Alisa M.V.; Elsner, Jonas; Meinecke, Peter; Biskup, Saskia; Chung, Brian H.Y.; Dombrowsky, Gregor; et al. (Nature, 2023)
Thousands of genetic variants in protein-coding genes have been linked to disease. However, the functional impact of most variants is unknown as they occur within intrinsically disordered protein regions that have poorly defined functions1–3. Intrinsically disordered regions can mediate phase separation and the formation of biomolecular condensates, such as the nucleolus4,5. This suggests that mutations in disordered proteins may alter condensate properties and function6–8. Here we show that a subset of disease-associated variants in disordered regions alter phase separation, cause mispartitioning into the nucleolus and disrupt nucleolar function. We discover de novo frameshift variants in HMGB1 that cause brachyphalangy, polydactyly and tibial aplasia syndrome, a rare complex malformation syndrome. The frameshifts replace the intrinsically disordered acidic tail of HMGB1 with an arginine-rich basic tail. The mutant tail alters HMGB1 phase separation, enhances its partitioning into the nucleolus and causes nucleolar dysfunction. We built a catalogue of more than 200,000 variants in disordered carboxy-terminal tails and identified more than 600 frameshifts that create arginine-rich basic tails in transcription factors and other proteins. For 12 out of the 13 disease-associated variants tested, the mutation enhanced partitioning into the nucleolus, and several variants altered rRNA biogenesis. These data identify the cause of a rare complex syndrome and suggest that a large number of genetic variants may dysregulate nucleoli and other biomolecular condensates in humans.
CRIS-Team Scopus Importer:2023-02-17

A NEW DIAGNOSTIC APPROACH TO HLA TESTING IN KIDNEY TRANSPLANT RECIPIENTS USING CULTURED URINE DERIVED TUBULAR CELLS - Spriewald, Bernd; Herrmann, Markus; Bach, Christian; Knaup, Karl; Krumbiegel, Mandy; Wiesmann da Silva Reis, André; Schiffer, Mario; Wiesener, Michael (Joint 34th European Immunogenetics and Histocompatibility and 31st British Society for Histocompatibility and Immunogenetics Conference, 2020)
CRIS-Team WoS Importer:2020-03-24

BDV Syndrome: An Emerging Syndrome with Profound Obesity and Neurodevelopmental Delay Resembling Prader-Willi Syndrome - Bosch, Elisabeth; Hebebrand, Moritz; Popp, Bernt; Penger, Theresa; Behring, Bettina; Cox, Helen; Towner, Shelley; Kraus, Cornelia; Wilson, William G.; Khan, Shagufta; Krumbiegel, Mandy; Ekici, Arif Bülent; et al. (Journal of Clinical Endocrinology and Metabolism, 2021)
Context: CPE encodes carboxypeptidase E, an enzyme that converts proneuropeptides and propeptide hormones to bioactive forms. It is widely expressed in the endocrine and central nervous system. To date, 4 individuals from 2 families with core clinical features including morbid obesity, neurodevelopmental delay, and hypogonadotropic hypogonadism, harboring biallelic loss-of-function (LoF) CPE variants, have been reported. Objective: We describe 4 affected individuals from 3 unrelated consanguineous families, 2 siblings of Syrian, 1 of Egyptian, and 1 of Pakistani descent, all harboring novel homozygous CPE LoF variants. Methods: After excluding Prader-Willi syndrome (PWS), exome sequencing was performed in both Syrian siblings. The variants identified in the other 2 individuals were reported as research variants in a large-scale exome study and in the ClinVar database. Computational modeling of all possible missense alterations allowed assessing CPE tolerance to missense variants. Results: All affected individuals were severely obese with neurodevelopmental delay and other endocrine anomalies. Three individuals from 2 families shared the same CPE homozygous truncating variant c.361Câ€ >â€ T, p.(Arg121∗), while the fourth carried the c.994del, p.(Ser333Alafs∗22) variant. Comparison of clinical features with previously described cases and standardization according to the Human Phenotype Ontology terms indicated a recognizable clinical phenotype, which we termed Blakemore-Durmaz-Vasileiou (BDV) syndrome. Computational analysis indicated high conservation of CPE domains and intolerance to missense changes. Conclusion: Biallelic truncating CPE variants are associated with BDV syndrome, a clinically recognizable monogenic recessive syndrome with childhood-onset obesity, neurodevelopmental delay, hypogonadotropic hypogonadism, and hypothyroidism. BDV syndrome resembles PWS. Our findings suggest missense variants may also be clinically relevant.
CRIS-Team Scopus Importer:2021-12-24
Keywords: BDV syndrome; carboxypeptidase E; CPE; hypogonadotropic hypogonadism; neurodevelopmental disorder; obesity

Beyond founder and truncting variants in TECPR2-associated disorder - Neuser, Sonja; Brechmann, Barbara; Heimer, Gali; Brosse, Ines; Schubert, Susanna; O'Grady, Lauren; Zech, Michael; Srivastava, Siddharth; Sweetser, David A.; Dincer, Yasemin; Mall, Volker; Winkelmann, Juliane; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2022)
CRIS-Team WoS Importer:2022-05-06

Clinical and molecular delineation of spondylocostal dysostosis type 3 - Schuhmann, Sarah; Koller, Heiko; Sticht, Heinrich; Kraus, Cornelia; Krumbiegel, Mandy; Uebe, Steffen; Ekici, Arif Bülent; Reis, André; Thiel, Christian (Clinical Genetics, 2021)
CRIS-Team Scopus Importer:2021-03-26

Clinical, neuroimaging, and molecular spectrum of TECPR2-associated hereditary sensory and autonomic neuropathy with intellectual disability - Neuser, Sonja; Brechmann, Barbara; Heimer, Gali; Broesse, Ines; Schubert, Susanna; O'Grady, Lauren; Zech, Michael; Srivastava, Siddharth; Sweetser, David A.; Dincer, Yasemin; Mall, Volker; Winkelmann, Juliane; et al. (Human Mutation, 2021)
Bi-allelic TECPR2 variants have been associated with a complex syndrome with features of both a neurodevelopmental and neurodegenerative disorder. Here, we provide a comprehensive clinical description and variant interpretation framework for this genetic locus. Through international collaboration, we identified 17 individuals from 15 families with bi-allelic TECPR2-variants. We systemically reviewed clinical and molecular data from this cohort and 11 cases previously reported. Phenotypes were standardized using Human Phenotype Ontology terms. A cross-sectional analysis revealed global developmental delay/intellectual disability, muscular hypotonia, ataxia, hyporeflexia, respiratory infections, and central/nocturnal hypopnea as core manifestations. A review of brain magnetic resonance imaging scans demonstrated a thin corpus callosum in 52%. We evaluated 17 distinct variants. Missense variants in TECPR2 are predominantly located in the N- and C-terminal regions containing β-propeller repeats. Despite constituting nearly half of disease-associated TECPR2 variants, classifying missense variants as (likely) pathogenic according to ACMG criteria remains challenging. We estimate a pathogenic variant carrier frequency of 1/1221 in the general and 1/155 in the Jewish Ashkenazi populations. Based on clinical, neuroimaging, and genetic data, we provide recommendations for variant reporting, clinical assessment, and surveillance/treatment of individuals with TECPR2-associated disorder. This sets the stage for future prospective natural history studies.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Human Phenotype Ontology; neurodevelopmental disorder; sensory autonomic neuropathy; spastic paraplegia; TECPR2

CRISPR/Cas9 mediated generation of human ARID1B heterozygous knockout hESC lines to model Coffin-Siris syndrome - Börstler, Tom; Wend, Holger; Krumbiegel, Mandy; Kavyanifar, Atria; Reis, André; Lie, Dieter Chichung; Winner, Beate; Turan, Sören (Stem Cell Research, 2020)
ARID1B haploinsufficiency induced by missense or nonsense mutations of ARID1B is a cause of Coffin-Siris syndrome (CSS), a neurodevelopmental disorder associated with intellectual disability. At present, no appropriate human stem cell model for ARID1B-associated CSS has been reported. Here, we describe the generation and validation of ARID1B+/- hESCs by introducing out of frame deletions into exon 5 or 6 of ARID1B with CRISPR/Cas9 genome editing. These ARID1B+/- hESC lines allow to study the pathophysiology of ARID1B-associated CSS in 2D and 3D models of human neurodevelopment.
CRIS-Team Scopus Importer:2020-07-24

CRISPR/Cas9 mediated generation of human ARID1B heterozygous knockout hESC lines to model Coffin-Siris syndrome - Börstler, Tom; Wend, Holger; Krumbiegel, Mandy; Kavyanifar, Atria; Wiesmann da Silva Reis, André; Lie, Dieter Chichung; Winner, Beate; Turan, Sören (Stem Cell Research, 2020)
ARID1B haploinsufficiency induced by missense or nonsense mutations of ARID1B is a cause of Coffin-Siris syndrome (CSS), a neurodevelopmental disorder associated with intellectual disability. At present, no appropriate human stem cell model for ARID1B-associated CSS has been reported. Here, we describe the generation and validation of ARID1B(+/-) hESCs by introducing out of frame deletions into exon 5 or 6 of ARID1B with CRISPR/Cas9 genome editing. These ARID1B(+/-) hESC lines allow to study the pathophysiology of ARID1B-associated CSS in 2D and 3D models of human neurodevelopment.

CRISPR/Cas9 mediated generation of human ARID1B heterozygous knockout hESC lines to model Coffin-Siris syndrome. - Turan, Soeren; Winner, Beate; Winner, Beate; Krumbiegel, Mandy; Wiesmann da Silva Reis, André; Lie, Dieter Chichung; Börstler, Tom; Wend, Holger; Krumbiegel, Mandy; Kavyanifar, Atria; Reis, Andre; Lie, Dieter Chichung (Stem Cell Research, 2020)
ARID1B haploinsufficiency induced by missense or nonsense mutations of ARID1B is a cause of Coffin-Siris syndrome (CSS), a neurodevelopmental disorder associated with intellectual disability. At present, no appropriate human stem cell model for ARID1B-associated CSS has been reported. Here, we describe the generation and validation of ARID1B+/- hESCs by introducing out of frame deletions into exon 5 or 6 of ARID1B with CRISPR/Cas9 genome editing. These ARID1B+/- hESC lines allow to study the pathophysiology of ARID1B-associated CSS in 2D and 3D models of human neurodevelopment.

Deletion 7q31.2q31.31 segregating in a family with speech and language deficiencies - Rieger, Melissa; Krumbiegel, Mandy; Reuter, Miriam; Schützenberger, Anne; Reis, André; Zweier, Christiane (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Different MAPT haplotypes influence expression of total MAPT in postmortem brain tissue - Tauber, Christina V.; Schwarz, Sigrid C.; Rösler, Thomas W.; Arzberger, Thomas; Gentleman, Steve; Windl, Otto; Krumbiegel, Mandy; Reis, André; Ruf, Viktoria C.; Herms, Jochen; Höglinger, Günter U. (Acta Neuropathologica Communications, 2023)
The MAPT gene, encoding the microtubule-associated protein tau on chromosome 17q21.31, is result of an inversion polymorphism, leading to two allelic variants (H1 and H2). Homozygosity for the more common haplotype H1 is associated with an increased risk for several tauopathies, but also for the synucleinopathy Parkinson’s disease (PD). In the present study, we aimed to clarify whether the MAPT haplotype influences expression of MAPT and SNCA, encoding the protein α-synuclein (α-syn), on mRNA and protein levels in postmortem brains of PD patients and controls. We also investigated mRNA expression of several other MAPT haplotype-encoded genes. Postmortem tissues from cortex of fusiform gyrus (ctx-fg) and of the cerebellar hemisphere (ctx-cbl) of neuropathologically confirmed PD patients (n = 95) and age- and sex-matched controls (n = 81) were MAPT haplotype genotyped to identify cases homozygous for either H1 or H2. Relative expression of genes was quantified using real-time qPCR; soluble and insoluble protein levels of tau and α-syn were determined by Western blotting. Homozygosity for H1 versus H2 was associated with increased total MAPT mRNA expression in ctx-fg regardless of disease state. Inversely, H2 homozygosity was associated with markedly increased expression of the corresponding antisense MAPT-AS1 in ctx-cbl. PD patients had higher levels of insoluble 0N3R and 1N4R tau isoforms regardless of the MAPT genotype. The increased presence of insoluble α-syn in PD patients in ctx-fg validated the selected postmortem brain tissue. Our findings in this small, but well controlled cohort of PD and controls support a putative biological relevance of tau in PD. However, we did not identify any link between the disease-predisposing H1/H1 associated overexpression of MAPT with PD status. Further studies are required to gain a deeper understanding of the potential regulatory role of MAPT-AS1 and its association to the disease-protective H2/H2 condition in the context of PD.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Gene expression; H1 and H2 haplotype; MAPT; Parkinson’s disease; Postmortem human brain; Protein level; Synucleins; Tau protein

Expanding the phenotype of 12q21 deletions: A role of BTG1 in speech development? - Blum, Katalin; Krumbiegel, Mandy; Kraus, Cornelia; Reis, André; Hüffmeier, Ulrike (European Journal of Medical Genetics, 2023)
We report on a female individual with feeding difficulties, constipation, poor overall growth, periventricular lesions resembling gliosis in brain MRI, recurrent otitis media with palsy of facial nerve, distinct facial features, and pronounced delay in speech development. The latter was the most prominent feature. Molecular karyotyping revealed a heterozygous de novo deletion of 4.353 Mb at chromosome 12q21.33q22. This report expands the number of described individuals with heterozygous deletions at 12q21.33, their clinical spectrum and highlights the clinical variability, even in individuals with deletion of the same genes. Furthermore, our findings indicate a role of BTG1 (OMIM *109580) in speech development.
CRIS-Team Scopus Importer:2023-02-24
Keywords: 12q21.33; Microdeletion; Speech developmental delay

Further clinical and molecular delineation of spondylocostal dysostosis type 3 - Schuhmann, Sarah; Koller, H.; Sticht, Heinrich; Kraus, Cornelia; Krumbiegel, Mandy; Uebe, Steffen; Ekici, Arif Bülent; Reis, André; Thiel, C. T. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Generation of a homozygous and a heterozygous SNCA gene knockout human-induced pluripotent stem cell line by CRISPR/Cas9 mediated allele-specific tuning of SNCA expression - Schneider, Yanni; Turan, Soeren; Koller, Aron; Krumbiegel, Mandy; Farrell, Michaela; Plotz, Sonja; Winkler, Jürgen; Xiang, Wei (Stem Cell Research, 2022)
Aggregation of alpha-synuclein (aSyn) is closely linked to Parkinson's disease, probably due to the loss of physiological functions and/or gain of toxic functions of aggregated aSyn. Significant efforts have been made elucidating the physiological structure and function of aSyn, however, with limited success thus far in human -derived cells, partly because of restricted resources. Here, we developed two human-induced pluripotent stem cell lines using CRISPR/Cas9-mediated allele-specific frame-shift deletion of the aSyn encoding gene SNCA, resulting in homo-and heterozygous SNCA knockout. The generated cell lines are promising cellular tools for studying aSyn dosage-dependent functions and structural alterations in human neural cells.
CRIS-Team WoS Importer:2022-11-18

Microdeletions at 19p13.11 in four individuals with neurodevelopmental delay - Rieger, Melissa; Moutton, Sebastien; Verheyen, Sarah; Speicher, Michael; Leheup, Bruno; Bonnet, Celine; Steindl, Katharina; Boneda, Beatrice; Rauch, Anita; Krumbiegel, Mandy; Reis, André; Hüffmeier, Ulrike (EUROPEAN JOURNAL OF HUMAN GENETICS, 2022)
CRIS-Team WoS Importer:2022-05-06

Microdeletions at 19p13.11p12 in five individuals with neurodevelopmental delay - Rieger, Melissa; Moutton, Sébastien; Verheyen, Sarah; Steindl, Katharina; Popp, Bernt; Leheup, Bruno; Bonnet, Céline; Oneda, Beatrice; Rauch, Anita; Reis, André; Krumbiegel, Mandy; Hüffmeier, Ulrike (European Journal of Medical Genetics, 2023)
Only few copy number variants at chromosome 19p13.11 have been reported, thus associated clinical information is scarce. Proximal to these copy number losses, we now identified deletions in five unrelated individuals with neurodevelopmental disorders. They presented with psychomotor delay as well as behavioral and sleeping disorders, while complex cardiovascular, skeletal, and various other malformations were more variable. Dysmorphic features were rather unspecific and not considered as a recognizable gestalt. Neither of the analyzed parents carried their offsprings' deletions, indicating de novo occurrence. The deletion sizes ranged between 0.7 and 5.2 Mb, were located between 18 and 24 megabases from the telomere, and contained a variable number of protein-coding genes (n = 25–68). Although not all microdeletions shared a common region, the smallest common overlap of some of the deletions provided interesting insights in the chromosomal region 19p13.11p12. Diligent literature review using OMIM and Pubmed did not identify a satisfying candidate gene for neurodevelopmental disorders. In the literature, a de novo in-frame deletion in MAU2 was considered pathogenic in an individual with Cornelia de Lange syndrome. Therefore, the clinical differential diagnosis of this latter syndrome in one individual and the encompassment of MAU2 in three individuals' deletions suggest clinical and genetic overlap with this specific syndrome. Three of the four here reported individuals with deletion encompassing GDF1 had different congenital heart defects, suggesting that this gene's haploinsufficiency might contribute to the cardiovascular phenotype, however, with reduced penetrance. Our findings indicate an association of microdeletions at 19p13.11/ 19p13.11p12 with neurodevelopmental disorders, variable symptoms, and malformations, and delineate the phenotypic spectrum of deletions within this genomic region.
CRIS-Team Scopus Importer:2022-12-16
Keywords: 19p13.11p12; Deletion; GDF1; Malformation; MAU2; NDD

Severe manifestation of Rauch-Azzarello syndrome associated with biallelic deletion of CTNND2 - Pauly, Melissa; Krumbiegel, Mandy; Trumpp, Sandra; Braig, Sonja; Rupprecht, Thomas; Kraus, Cornelia; Uebe, Steffen; Reis, André; Vasileiou, Georgia (Clinical Genetics, 2024)
CTNND2 encodes δ-catenin, a component of an adherens junction complex, and plays an important role in neuronal structure and function. To date, only heterozygous loss-of-function CTNND2 variants have been associated with mild neurodevelopmental delay and behavioral anomalies, a condition, which we named Rauch-Azzarello syndrome. Here, we report three siblings of a consanguineous family of Syrian descent with a homozygous deletion encompassing the last 19 exons of CTNND2 predicted to disrupt the transcript. All presented with severe neurodevelopmental delay with absent speech, profound motor delay, stereotypic behavior, microcephaly, short stature, muscular hypotonia with lower limb hypertonia, and variable eye anomalies. The parents and the fourth sibling were heterozygous carriers of the deletion and exhibited mild neurodevelopmental impairment resembling that of the previously described heterozygous individuals. The present study unveils a severe manifestation of CTNND2-associated Rauch-Azzarello syndrome attributed to biallelic loss-of-function aberrations, clinically distinct from the already described mild presentation of heterozygous individuals. Furthermore, we demonstrate novel clinical features in homozygous individuals that have not been reported in heterozygous cases to date.
CRIS-Team Scopus Importer:2024-04-19
Keywords: biallelic; CTNND2; LoF; NDD; neurodevelopmental delay; δ-catenin

SRD5A3-CDG: Twins with an intragenic tandem duplication - Rieger, Melissa; Türk, Matthias; Kraus, Cornelia; Uebe, Steffen; Ekici, Arif Bülent; Krumbiegel, Mandy; Huchzermeyer, Cord; Wiesmann da Silva Reis, André; Thiel, Christian (European Journal of Medical Genetics, 2022)
Steroid 5α-reductase type 3 congenital disorder of glycosylation (SRD5A3-CDG) is a rare metabolic disease mainly characterized by psychomotor disability, visual impairment, and variable eye malformations caused by bi-allelic pathogenic variants in SRD5A3. So far, only 23 distinct mutations were described. Exome sequencing in 32-year old monozygotic male twins revealed only the heterozygous splice variant c.562+3delG in SRD5A3, but no second variant. The twins presented with psychomotor deficit and a complex eye disease including retinal dystrophy, pallor of the papilla, nystagmus, and strabismus suggestive of SRD5A3-CDG. Only when applying exome-based copy number analysis, we identified as a second compound heterozygous variant a previously not reported tandem duplication of exons 2–4 in SRD5A3. Next to the typical skeletal anomalies of SRD5A3-CDG such as kyphosis and scoliosis, extension deficits of the proximal interphalangeal (PIP) joints IV were observed. Since similar contractures were described once in a patient with SRD5A3-CDG, we suggest that this rare symptom is possibly associated with SRD5A3-CDG. Our findings further expand the mutational and clinical spectrum of SRD5A3-CDG and emphasize the importance of an intragenic copy number analysis in patients with strong clinical suspicion of SRD5A3-CDG and only one detectable sequence variant.
CRIS-Team Scopus Importer:2022-04-15
Keywords: CDG; Exon duplication; SRD5A3

Tetrasomy of SCN2A associated with refractory neonatal epileptic encephalopathy - Krumbiegel, Mandy; Trollmann, Regina; Mammadova, Dilbar; Schnell, Alexander; Kraus, Cornelia; Ekici, Arif Bülent; Reis, André; Zweier, Christiane (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22